OPIS PRZYPADKU/CASE REPORTNephrolithiasis as a first manifestation of primary Sjögren’s syndrome. - Mazurek, Marcin; Majdan, Maria; Piotrowski, Mariusz; Chudzik, Dariusz (Reumatologia/Rheumatology, 2005)
Renal involvement is a frequent extra glandular manifestation of primary Sjögren syndrome (pSS) and may precede the onset of subjective sicca syndrome. The main manifestation of renal involvement in pSS is tubulo-interstitial nephritis, with results in tubular defects. It may manifest as distal renal tubular acidosis, proximal renal tubular acidosis or isolated proximal tubular dysfunctions leading to urolithiasis and nephrocalcinosis. We report three women aged 32, 46 and 37 years old with pSS. The diagnose of pSS was done respectively 6, 10 and 7 year after diagnose of urolithiasis. The reason of the rheumatologic consultation were: in two cases arthralgias, and in one case pericarditis sicca. All had hyposthenuria, an urinary pH over 6.5, hyperchloraemic metabolic acidosis with high anion gap, hypokalaemia. All reported recurrent urinary tract infections. We described the mechanisms of the development of urolithiasis in pSS, and reasons of the delay of the diagnose of pSS.